Factors influencing the usage of 3G mobile services in Taiwan - Liao, Chun-Hsiung; Tsou, Chun-Wang; Huang, Ming-Feng (Online information review, 2007)
Purpose - The purpose of this study is to analyse factors influencing subscribers' usage of 3G mobile services in Taiwan.Design methodology approach - The research model, based on a technology acceptance model (TAM) and added perceived enjoyment, was tested by means of a two-stage structure equation modelling approach. Data were collected from 532 respondents via a web questionnaire survey.Findings - The findings indicate that perceived usefulness, perceived ease of use and perceived enjoyment are positively related to attitude, and perceived enjoyment has a positive influence on perceived usefulness.Practical implications - The findings suggest users of 3G mobile services need to be provided with more diverse and entertaining ways of communicating, which are at the same time easily accessible and convenient to use.Originality value - A new correlation from perceived enjoyment to perceived usefulness was found to have a significant effect. This finding indicates enjoyment as a key factor influences customers' adoption of 3G services.